Analysis of health economics assessment reports for pharmaceuticals in France - understanding the underlying philosophy of CEESP assessment - Mondher Toumi; Anastasiia Motrunich; Aurélie Millier; Cécile Rémuzat; Christos Chouaid; Bruno Falissard; Samuel Aballéa (Taylor & Francis Group, 2017)
Background: Despite the guidelines for Economic and Public Health Assessment Committee (CEESP) submission having been available for nearly six years, the dossiers submitted continue to deviate from them, potentially impacting product prices. Objective: to review the reports published by CEESP, analyse deviations from the guidelines, and discuss their implications for the pricing and reimbursement process. Study design: CEESP reports published until January 2017 were reviewed, and deviations from the guidelines were extracted. The frequency of deviations was described by type of methodological concern (minor, important or major). Results: In 19 reports, we identified 243 methodological concerns, most often concerning modelling, measurement and valuation of health states and results presentation and sensitivity analyses; nearly 63% were minor, 33% were important and 4.5% were major. All reports included minor methodological concerns, and 17 (89%) included at least one important and/or major methodological concern. Global major methodological concerns completely invalidated the analysis in seven dossiers (37%). Conclusion: The CEESP submission dossiers fail to adhere to the guidelines, potentially invalidating the health economics analysis and resulting in pricing negotiations. As these negotiations tend to be unfavourable for the manufacturer, the industry should strive to improve the quality of the analyses submitted to CEESP.